ANALISIS KEMAMPUAN DAYA TAHAN V02 MAX PEMAIN SEPAK BOLA DI KLUB BENGKULU MUDA FC KOTA BENGKULU - Nikentry, Nikentry; Sumantri, Ajis; Juwita, Juwita (Educative Sportive, 2024)
This study aims to determine the VO2 Max Endurance Ability of Football Players at Bengkulu Muda Fc Club, Bengkulu City. This type of research is qualitative descriptive research. The research sample amounted to 25 people. The instrument used in this research is the Bleep Test / Multi-Stage. Where the results of the VO2 Max Endurance Ability of Football Players at Bengkulu Muda Fc Club, Bengkulu City in this study show the classification "High" to "Low". Then where the results of the final VO2 Max Endurance Ability Test of Football Players at Bengkulu Muda Fc Club Bengkulu City, as follows: 64% (16 players) in the Fair category and 28% (7 players) in the Medium category and 8% (2 players) in the Low category. Based on these results, it can be concluded that the VO2 Max Endurance Ability of Football players at Bengkulu City Young Bengkulu Club carried out by 25 players of Bengkulu City Young Bengkulu Club in the Sufficient category, namely 16 players or with a percentage of 64%.